The Contribution of Serum Anti–cyclic Citrullinated Peptide Antibody and Matrix Metalloproteinase-3 in Predicting the Activity of Rheumatoid Arthritis Disease - Al-Derzi, Aida R. (Journal of the Faculty of Medicine Baghdad, 2017)
Background: Rheumatoid arthritis is an autoimmune disease characterized by chronic synovial inflammation. The insufficient immune clearance of the apoptotic cell results into the formation of anti-cyclic citrullinated peptide antibodies which may play a critical role in the initiations of inflammatory responses. These antibodies together with Matrix Metalloproteinase-3 play an important role in joint destruction in rheumatoid arthritis disease. Objectives: to study the value of anti-cyclic citrullinated peptide antibodies, and Matrix Metalloproteinase-3 in differentiation between active and inactive rheumatoid arthritis. Patients and Methods: A cross- sectional study was conducted on 60 Iraqi patients with rheumatoid arthritis (16 males and 44 females) aging from 29 to 74 years who presented to the Rheumatology Consultation Clinic of Baghdad Teaching Hospital / Medical City during the period of July 2013 to the end of October 2013. The patients were divided, according to rheumatoid arthritis activity depending on Disease Activity Score 28 and erythrocyte sedimentation rate, into two groups: 30 patients with active rheumatoid arthritis and the other 30 patients with inactive rheumatoid arthritis. Quantitative sandwich enzyme immunoassay technique was used to measure serum level of anti-cyclic citrullinated peptide antibodies, and Matrix Metalloproteinase-3. Results: The means concentration of anti-cyclic citrullinated peptide antibodies, and Matrix Metalloproteinase-3 were significantly higher in rheumatoid arthritis cases with active disease compared to those with inactive disease. The disease activity index DAS28 showed a statistically significant strong positive (direct) linear correlation with serum MMP3 (r=0.762) and serum ACCP (r=0.806). In addition, serum MMP3 showed a statistically significant moderately strong positive (direct) linear correlation with serum ACCP (r=0.64). Both serum MMP3 and ACCP had a higher validity than blood ESR (which is used itself in calculating DAS28) is predicting an active disease status. Conclusion: Anti-cyclic citrullinated peptide antibodies and Matrix Metalloproteinase-3 could be useful biological markers for assessment of rheumatoid arthritis disease activity.